Analisis Kesempatan Kerja Dan Produktivitas Tenaga Kerja Pada Sektor Pertanian Di Provinsi Aceh - Sofyan Sofyan; Elvira Iskandar; Zakia Izzati (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
ABSTRACT. Agriculture is a leading sector in Aceh economy, showed by the large number of people who work in agricultural areas. This sector contribute the high number of gross domestic product (GDP) to Aceh Province. The problems appear when the growth of community do not followed by the growth of employment. This will cause the increasing of unemployment rate in Aceh Province.This study analyzed the development of agricultural employment and labor productivity in Aceh Province. The analysis was also conducted to calculate the influence of employment to GDP in agricultural sector. Time series data were used from 2003 to 2012 with a simple linear regression method.The results showed the significantly decreasing of agricultural employment by 16.635 people per year and the increasing of agricultural labor productivity by IDR 11.699.353/ year. The employment has a significant influence to GDP in agricultural sector but it has a negative relationship. The additional increasing of employment will decrease the GDP by IDR 1.255.000 per year. It means that the increasing of labour should be balanced and followed by another production factors to increase the total output of agricultural sector in Aceh Province.